Perfil de expressão de lncRNAs e sua relação com a resposta à quimiorradioterapia em câncer de colo uterino: Potenciais biomarcadores para diagnóstico e prognóstico - Duarte, Bruna Custódio Dias (2024)
Cervical cancer (CC) is predominantly induced by persistent infections of certain oncogenic genotypes of the human papillomavirus (HPV) and represents a significant global public health challenge. The World Health Organization (WHO) has established a strategic plan aimed at eliminating CC as a public health problem by the year 2100. However, despite the proven efficacy of the HPV vaccine, implementation on a global scale faces obstacles due to limited accessibility to vaccination and prevalent misinformation. The treatment of CC is influenced by the stage of the disease, with an often unfavorable prognosis in cases of advanced or recurrent disease. Therefore, the discovery and application of biomarkers in CC is fundamental to clinical decision making, allowing for a more targeted approach, improving therapeutic efficacy and optimizing the monitoring of disease progression. The present study sought to explore the potential of long non-coding RNAs (lncRNAs) in CC, focusing on the identification and characterization of these lncRNAs, the elucidation of their regulatory mechanisms and molecular interactions, and the analysis of their expression patterns in patients who showed variable responses to chemoradiotherapy. To this end, non-stem cells from CCU were isolated using flow cytometry sorting and used for total RNA extraction. The RNA was used to construct libraries which were subsequently sequenced using the Illumina Nextseq 550. Differential expression analysis revealed 417 lncRNAs with distinct expression patterns between samples from patients who responded to treatment and those who did not. The analyses revealed that these lncRNAs interact significantly with several biomolecules that are crucial for the progression of CC and therapeutic resistance. Statistical analyses made it possible to correlate the expression profile of these lncRNAs with treatment efficacy. The lncRNAs ENSG00000267838, ENSG00000266340 and FRMD6-AS1 were shown to influence the response to chemoradiotherapy treatment through their expression profile. ENSG00000267838 was able to differentiate the groups of responders and non-responders through its negative and positive regulation, respectively. These results indicate that these lncRNAs may play a fundamental role in modulating the therapeutic response, with the potential to act as biomarkers in the diagnosis, prognosis and monitoring of the progression of cervical carcinoma. However, additional studies and validation processes are imperative to corroborate this evidence.